Investment Decision: Profitability and Non-Public Ownership in Value Relevance of Accounting Information - Chusnia, Vina Maulidah; Pujiono, Pujiono (Jurnal Bisnis Mahasiswa, 2024)
The aim of this study is to study the impact of the relevance of the value of accounting information on investment decisions. The relevance of the value of accounting information is measured by the EPS, ROA, and Non-Public Ownership profitability ratio, while investment decisions are scattered with the share price. The research sample consists of 27 companies in the Food and Beverage Industry Subsector listed in the EIB during 2015-2022. Data analysis methods include classical assumption tests, double linear regression analysis, F tests, and t tests using SPSS 29 software. Research results show that EPS and ROA have an effect on stock prices, so it can be a reference for investors in making investment decisions. While Non-Public Ownership has no influence on stock prices, investors need to undertake in-depth analysis of corporate information and operational performance that is not fully disclosed to the public.